Collective Bargaining and Inflation - Saunders, George (Relations industrielles / Industrial Relations, 1968)
Pending the results of such further research it can only be concluded at this juncture that, given the nature of the Canadian economy and the system of wage determination, there is no reason to believe that the contribution of collective bargaining to recent price developments was any greater than that of other factors in the inflationary process.